In uncertain times : American foreign policy after the Berlin Wall and 9/11 - Leffler, Melvyn P., 1945-; Legro, Jeffrey (Cornell paperbacks., 2011)
In Uncertain Times considers how policymakers react to dramatic developments on the world stage. Few expected the Berlin Wall to come down in November 1989; no one anticipated the devastating attacks on the World Trade Center and the Pentagon in September 2001. American foreign policy had to adjust quickly to an international arena that was completely transformed. Melvyn P. Leffler and Jeffrey W. Legro have assembled an illustrious roster of officials from the George H.W. Bush, Clinton, and George W. Bush administrations-Robert B. Zoellick, Paul Wolfowitz, Eric S. Edelman, Walter B. Slocombe, and Philip Zelikow. These policymakers describe how they went about making strategy for a world fraught with possibility and peril. They offer provocative reinterpretations of the economic strategy advanced by the George H.W. Bush administration, the bureaucratic clashes over policy toward the breakup of the USSR, the creation of the Defense Policy Guidance of 1992, the expansion of NATO, the writing of the National Security Strategy Statement of 2002, and the invasion of Iraq in 2003.A group of eminent scholars address these same topics. Bruce Cumings, John Mueller, Mary Elise Sarotte, Odd Arne Westad, and William C. Wohlforth probe the unstated assumptions, the cultural values, and the psychological makeup of the policymakers. They examine whether opportunities were seized and whether threats were magnified and distorted. They assess whether academicians and independent experts would have done a better job than the policymakers did. Together, policymakers and scholars impel us to rethink how our world has changed and how policy can be improved in the future. Contributors: Bruce Cumings, University of Chicago; Eric S. Edelman, Center for Strategic and Budgetary Assessments; Melvyn P. Leffler, University of Virginia; Jeffrey W. Legro, University of Virginia; John Mueller, Ohio State University; Mary Elise Sarotte, University of Southern California; Walter B. Slocombe, Council on Foreign Relations and Caplin & Drysdale; Odd Arne Westad, London School of Economics and Political Science; William C. Wohlforth, Dartmouth College; Paul Wolfowitz, American Enterprise Institute for Public Policy Research; Philip Zelikow, University of Virginia; Robert B. Zoellick, World Bank Group.